Tropical cyclones facilitate recovery of forest leaf area from dry spells in East Asia - Chen, Yi-Ying; Luyssaert, Sebastiaan (Biogeosciences, 2023)
Forests disturbance by tropical cyclones is mostly documented by field studies of exceptionally strong cyclones and satellite-based approaches attributing decreases in leaf area. By starting their analysis from the observed damage, these studies are biased and may, therefore, limit our understanding of the impact of cyclones in general. This study overcomes such biases by jointly analyzing the cyclone tracks, climate reanalysis, and changes in satellite-based leaf area following the passage of 140 ± 41 cyclones. Sixty days following their passage, 18 ± 8 % of the cyclones resulted in a decrease and 48 ± 18 % showed no change in leaf area compared to nearby forest outside the storm track. For a surprising 34 ± 7 % of the cyclones, an increase in leaf area was observed. Cyclones resulting in higher leaf area in their affected compared to their reference area coincided with an atmospheric pressure dipole steering the cyclone towards a region experiencing a dry spell caused by the same dipole. When the dipole was present, the destructive power of cyclones was offset by their abundant precipitation enabling forest canopies in the affected area to recover faster from the dry spell than canopies in the reference area. This study documents previously undocumented widespread antagonist interactions on forest leaf area between tropical cyclones and droughts.